2021
DOI: 10.1093/ajh/hpab111
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Renin–Angiotensin–Aldosterone Inhibitors on Early Outcomes of Hypertensive COVID-19 Patients: A Randomized Triple-Blind Clinical Trial

Abstract: Background The role of angiotensin-converting enzyme inhibitors (ACEis) and angiotensin receptor blockers (ARBs) has been addressed in some studies related to the current coronavirus disease-2019 (COVID-19) pandemic with possible higher severity and mortality in patients with hypertension. A triple-blind randomized controlled trial was designed to evaluate the effects of these medications on the COVID-19 progression. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(49 citation statements)
references
References 15 publications
2
47
0
Order By: Relevance
“…Ten studies 33 , 34 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 57 investigated ACEIs/ARBs, with only 1 study (102 patients) 33 investigating COVID‐19 infectivity. Compared to standard of care, the ACEI ramipril (initial dose 2.5 mg/d, titrated up to 10 mg/d), when newly initiated, was reported to have no effect on COVID‐19 infectivity (hazard ratio 1.15, 95% CI 0.35 to 3.77).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Ten studies 33 , 34 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 57 investigated ACEIs/ARBs, with only 1 study (102 patients) 33 investigating COVID‐19 infectivity. Compared to standard of care, the ACEI ramipril (initial dose 2.5 mg/d, titrated up to 10 mg/d), when newly initiated, was reported to have no effect on COVID‐19 infectivity (hazard ratio 1.15, 95% CI 0.35 to 3.77).…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies 34 , 36 , 38 , 40 , 41 , 42 , 57 investigated whether ACEI/ARB exposure (both treatment‐experienced and ‐naïve patients) affected length of hospitalization. One study, 38 reported only medians and a hazard ratio and could therefore not be included in the primary meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…AUC, mean of SOFA were significantly lower in the discontinuation group. Najmeddin, 2021 [ 27 ] Iran Patients on ACEI or ARB therapy 64 Triple blind RCT Continuation or Discontinuation (1:1) ACEI or ARB No effect on the days of ICU or ward admission, the discharge rate, and readmission rates. Puskarich, 2021 [ 28 ] USA Outpatients with not already taking ACEI or ARB 117 Double-blind RCT Losartan or placebo (1:1) ARB (Losartan 25 mg twice daily) No effect on hospitalization, functional status, dyspnea, temperature, and viral load.…”
Section: Randomized Trials On the Effects Of Ras Inhibitors On Covid-19mentioning
confidence: 99%